The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s40064-016-3674-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful ceritinib treatment in a man with MPE and an ALK fusion gene mutation after multiple treatments

Abstract: Introduction Ceritinib is a second-generation anaplastic lymphoma kinase (ALK) inhibitor. It inhibits two of the most common ALK-mutants that confer resistance to crizotinib. Ceritinib was approved by Food and Drug Administration in April 2014. However, the efficacy of ceritinib in Asian patients have not been widely studied. Decrease of malignant pleural effusion (MPE) has been rarely reported after treatment with ceritinib.Case descriptionA 50-year old man diagnosed with stage IV lung adenocarcinoma presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Therapy could be targeted on an oncogene coming from a fusion of two genes: EML 4 (echinoderm microtubule-associated protein-like 4) and ALK (anaplastic lymphoma kinase), and inhibitors of its activity - crizotinib or ceritinib [143]. There have been reports of success in the treatment of MPE with these drugs in patients in whom other treatments have been found to be ineffective [144]. Sun et al reported a woman with a locally advanced adenocarcinoma of the lung and a bloody pleural effusion treated with a drainage (approximately 1000 ml/day) that did not respond to chemotherapy.…”
Section: Potential New Treatment Options For Mpementioning
confidence: 99%
“…Therapy could be targeted on an oncogene coming from a fusion of two genes: EML 4 (echinoderm microtubule-associated protein-like 4) and ALK (anaplastic lymphoma kinase), and inhibitors of its activity - crizotinib or ceritinib [143]. There have been reports of success in the treatment of MPE with these drugs in patients in whom other treatments have been found to be ineffective [144]. Sun et al reported a woman with a locally advanced adenocarcinoma of the lung and a bloody pleural effusion treated with a drainage (approximately 1000 ml/day) that did not respond to chemotherapy.…”
Section: Potential New Treatment Options For Mpementioning
confidence: 99%
“…Crizotinib and ceritinib are oral inhibitors of anaplastic lymphoma kinase (ALK), and they have been approved for the treatment of advanced cancer or metastatic NSCLC [59,60]. Only in some cases, it has been observed QTc prolongation, and therefore this anomaly is not frequent.…”
Section: Crizotinib and Ceritinibmentioning
confidence: 99%